Stimulating Mathematical Intuitions Through Games in Early Childhood Education (0 a 3 Years) - de Castro Hernández, Carlos; Flecha López, Gonzalo (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
We present here an approach to mathematics from 0 to 3 years, within the framework of embodied cognition, which may allow us to favour the early development of mathematical intuitions. We will explain the opportunities for the learning of mathematics that occur throughout the day in a nursery school. We will focus on a playing session with objects, close to heuristic play game, thus triggering the mathematical intuitions that toddlers can develop on their own. We will also expose how teachers, through game organisation and material selection, can promote the mathematical learning.
Keywords: Early Childhood Education; 0-3 year olds; Mathematics; heuristic play game; intuitive knowledge; embodied cognition